Women’s Political Rights Context in Gender and Human Rights Perspective - Diah Ratri Oktavriana (International Journal of Islamic Thought and Humanities, 2022)
Women have the right and the potential to make a real contribution to politics. However, the phenomenon of the increasing number of female figures in political contestation in the regions is still the pros and cons. Hence, the involvement of women still invites discussion, and debate, and often leaves doubts. Currently, the representation of women in the legislature is an essential concern of the government, one of which is through an affirmative action policy. In the political context, this affirmative action encouraged women's representation in the legislature. So that a regulation is needed that can guarantee and ensure the representation of women in parliament, both nationally and regionally. Starting with the ratification of the Convention on the Elimination of All Forms Of Discrimination Against Women (CEDAW) by Indonesia in 1984 through Law Number 7 of 1984 which provides special treatment to achieve gender equality, it has also been carried out through several other national laws and regulations, such as Law no. 12 of 2003 which regulates the political parties participating in the election to pay attention to the representation of women at least 30% in the nomination of members of the legislature.